Peal harbor December 7,1941 - Tourtellot, Arthur B. (United States : IRJA FILMS, INC. [production company] ; Kuala Lumpar : Lec Vision Enterprise [distributor], 1951)
Revealing documentary on the Pacific War beginning with Japanese preparations before the bombing of Pearl Harbor and ending with the U.S. dropping the atomic boms on Nagasaki and Hiroshima.
vol. 1. Kamikaze - vol. 2. December 7, 1941 - vol. 3. Appointment in Tokyo - vol. 4. Iwo Jima - vol. 5. The rise of the Japanese empire
The music in this production was used by special permission of the copyright owners
Editor, Peter Poor,Francoise Diot,Leo Zogling ; music, Norman Dello Jo ; photographed by, U.S. Navy